(3CSeGA GdQLGd GdVYaGA hGdeJQhcjfs - (3eMeO Hf Ydj Hf YHO GdQMef Hf CMeO Hf YHO Gddg , Gdecfi Hf ejjf GdUfgGLi s
(3ChdgG (B:s
(3ESMGb Hf YHOGddg Hf GHj aQhI , bGd GdfSGFi(B: (3eJQhc , hbGd gH(B: (3dGjMJL Hg , hef MOjKg(B: (3GdbGJd dGjQK QhGg J , hbGd (B: (3dGjUM s
(3BNQgG (B:s
(3jRjO GdQbGTi SHb PcQg bGd GdPgHi hZjQg(B: (3eJQhc, hbO SHb PcQg Qhi(B: (3GdEjeGf fUaGf fUa ai GdUHQ hfUa ai GdTcQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B29 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs